Paraneoplastic and Other Autoimmune Encephalitides: Antineuronal Antibodies, T Lymphocytes, and Questions of Pathogenesis - Greenlee, John E.; Carlson, Noel G.; Abbatemarco, Justin R.; Herdlevær, Ida; Clardy, Stacey L.; Vedeler, Christian A. (Frontiers in Neurology, 2022)
Autoimmune and paraneoplastic encephalitides represent an increasingly recognized cause of devastating human illness as well as an emerging area of neurological injury associated with immune checkpoint inhibitors. Two groups of antibodies have been detected in affected patients. Antibodies in the first group are directed against neuronal cell surface membrane proteins and are exemplified by antibodies directed against the N-methyl-D-aspartate receptor (anti-NMDAR), found in patients with autoimmune encephalitis, and antibodies directed against the leucine-rich glioma-inactivated 1 protein (anti-LGI1), associated with faciobrachial dystonic seizures and limbic encephalitis. Antibodies in this group produce non-lethal neuronal dysfunction, and their associated conditions often respond to treatment. Antibodies in the second group, as exemplified by anti-Yo antibody, found in patients with rapidly progressive cerebellar syndrome, and anti-Hu antibody, associated with encephalomyelitis, react with intracellular neuronal antigens. These antibodies are characteristically found in patients with underlying malignancy, and neurological impairment is the result of neuronal death. Within the last few years, major advances have been made in understanding the pathogenesis of neurological disorders associated with antibodies against neuronal cell surface antigens. In contrast, the events that lead to neuronal death in conditions associated with antibodies directed against intracellular antigens, such as anti-Yo and anti-Hu, remain poorly understood, and the respective roles of antibodies and T lymphocytes in causing neuronal injury have not been defined in an animal model. In this review, we discuss current knowledge of these two groups of antibodies in terms of their discovery, how they arise, the interaction of both types of antibodies with their molecular targets, and the attempts that have been made to reproduce human neuronal injury in tissue culture models and experimental animals. We then discuss the emerging area of autoimmune neuronal injury associated with immune checkpoint inhibitors and the implications of current research for the treatment of affected patients.